2019
DOI: 10.3201/eid2509.181811
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing ofSalmonellaMississippi and Typhimurium Definitive Type 160, Australia and New Zealand

Abstract: We used phylogenomic and risk factor data on isolates of Salmonella enterica serovars Mississippi and Typhimurium definitive type 160 (DT160) collected from human, animal, and environmental sources to elucidate their epidemiology and disease reservoirs in Australia and New Zealand. Sequence data suggested wild birds as a likely reservoir for DT160; animal and environmental sources varied more for Salmonella Mississippi than for Salmonella Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Similar phylogeographic relationships have been observed among other Salmonella serovars isolated from different geographic locations within the same country, including S. Typhimurium ( 33 ), S. Cerro ( 34 ), and S. Dublin ( 35 ), as well as between countries (e.g., S. Kentucky [ 36 ], S. Dublin [ 37 ], S. Typhi [ 38 ], and S. Typhimurium [ 39 ]). Ford and colleagues ( 16 ) also observed that S. Mississippi isolates from New Zealand (excluded from our analyses) represented a distinct phylogenetic clade separate from all Australian isolates, suggesting that there are likely additional phylogenetic clades of S. Mississippi outside those characterized here. Similarly, clade Bii S. Mississippi, which contained just 7 isolates from the United Kingdom, may also represent a distinct, geographically isolated clade representing a different region within the United Kingdom.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Similar phylogeographic relationships have been observed among other Salmonella serovars isolated from different geographic locations within the same country, including S. Typhimurium ( 33 ), S. Cerro ( 34 ), and S. Dublin ( 35 ), as well as between countries (e.g., S. Kentucky [ 36 ], S. Dublin [ 37 ], S. Typhi [ 38 ], and S. Typhimurium [ 39 ]). Ford and colleagues ( 16 ) also observed that S. Mississippi isolates from New Zealand (excluded from our analyses) represented a distinct phylogenetic clade separate from all Australian isolates, suggesting that there are likely additional phylogenetic clades of S. Mississippi outside those characterized here. Similarly, clade Bii S. Mississippi, which contained just 7 isolates from the United Kingdom, may also represent a distinct, geographically isolated clade representing a different region within the United Kingdom.…”
Section: Discussionsupporting
confidence: 49%
“…In this study, we describe the diversity of the geographically associated clades of S. Mississippi, which evolved from two separate MRCAs from serovars in clade B and clade A section Typhi. While infections with S. Mississippi are common in regions in the United States ( 14 , 18 ) and Australia ( 16 , 17 ), there were few reports about S. Mississippi in the United Kingdom ( 25 ). Gene presence/absence comparisons suggested that differentiation among isolates within the major clades is driven by the acquisition/loss of mobile elements such as prophage (clades Ai and Aii) and integration/conjugation elements (clade Bii).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations